Decision tree scoring system to guide selection for consumer preference in sweetpotato breeding trials - Nakitto, M.; Ssali, R.T.; Johanningsmeier, S.D.; Moyo, M.; Kock, H. de; Berget, I.; Okello, J.J.; Mayanja, S.; Tinyiro, S.E.; Mendes, T.; Benard, Y.; Chelengat, D.; et al. (Wiley, 2024)
Background Previously, a lexicon and protocol for quantitative descriptive analysis (QDA) was established for the Uganda sweetpotato breeding program. The implication of QDA scores for priority sensory attributes on consumer preference should be determined to interpret results efficiently and make decisions effectively. This study aimed to develop a gender-responsive decision tree to obtain an overall sweetpotato eating quality score to facilitate demand-led targeted breeding selection. It focused on Kamuli and Hoima districts (Uganda) and uses pre-lease advanced clones (‘NKB3’, ‘NKB105’, ‘NKB135’, ‘D11’, and ‘D20’), released varieties (‘NASPOT 8’, ‘NAROSPOT 1’), and landraces (‘Muwulu-Aduduma’, ‘Umbrella’).